Capabilities for Data-Driven Service Innovation - Schymanietz, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Martin Schymanietz explores dynamic capabilities that help organizations to cope with the challenges and chances of the utilization of data for service provision. Data-driven service innovation provides a fruitful pathway for organizations to extend their current offerings, deepen customer relationships and increase revenues. He examines the nature of data-driven service innovation, accompanied challenges and identifies relevant actors and their roles on an individual level. This approach helps organizations to develop dynamic capabilities based on individual actors that in sum shape the whole organization.<br
Keywords: Capabilities for Data-Driven Service Innovation; Data-driven service innovation; Digitalization; Dynamic capabilities; Co-creation; Actors; Qualitative research; Case study research; Delphi study